THEORETICAL ASPECTS OF STATE REGULATION OF SMALL AND MEDIUM BUSINESSES - Kucheriava, Karina; Orel, Yurii (Pressing Problems of Public Administration, 2021)
In most countries of the world, the development of entrepreneurship attracts attention of public authorities. But the parameters of the functioning of economic entities are constantly changing, as well as the long-term goals of economic policy of the state for the development of entrepreneurship. Therefore, the issue of rethinking the theoretical aspects of the regulation of the small and medium business sector needs special attention and has independent scientific significance. An overview of the business sector in Ukraine shows that in the national economy, at least, the basic prerequisites and requirements for the functioning and development of small and medium enterprises have been created. For many years, the state has been reforming the service for business sector. There are significant changes in the relationship and distribution of responsibilities to ensure sustainable social dynamics between the state, business and society. Based on the above, the state regulation of small and medium businesses means the purposeful influence of the state on the relations of economic entities through rule-making and positive legal influence, the organization of state bodies that carry out this regulation in cooperation with local governments, small entities and medium-sized businesses and their associations. The purpose of regulation is the formation of a competitive, innovative sector of small and medium enterprises and the formation of a culture of entrepreneurship. State policy on the development of small and medium enterprises requires the formation of appropriate mechanisms for its implementation. From the author’s point of view, the mechanism of state regulation of small and medium businesses is a component of state economic policy and is a set of measures, methods, tools and forms of state influence on business entities to create such socio-economic conditions for their operation that ensure the development of powerful layer of small and medium forms of entrepreneurship, able to fully perform their economic, resource, organizational, innovative, social and political functions.